Endogenous trade participation with incomplete exchange rate pass-through - Yuko Imura (Bank of Canada, 2013)
This paper investigates the implications of endogenous trade participation for international business cycles, trade flow dynamics and exchange rate pass-through when price adjustments are staggered across firms. I develop a two-country dynamic stochastic general equilibrium model wherein firms make state-dependent decisions on entry and exit in the export market and the frequency of price adjustment is time-dependent. Consistent with recent empirical findings, producers of traded goods in this model differ in their productivities, trade status and prices. At the aggregate level, quantitative properties of the model successfully reproduce some important characteristics of international business cycle moments in data. In contrast to previous findings in the literature, my model reveals that the inclusion of exporter entry and exit generates large, immediate responses in the number of exporters, export volumes and the export price index following aggregate shocks. I trace this result to the micro-level price stickiness present in my model but absent in existing models of endogenous trade participation. Moreover, I show that productivity heterogeneity rather than price age differences plays a dominant role in firms' export decisions, and hence the additional realism of endogenous trade participation in the model does not mitigate incomplete exchange rate pass-through arising from nominal rigidity. This suggests that exporter characteristics, market structure and pricing conventions may be critical in analyzing the role of endogenous trade participation for international business cycles and exchange rate pass-through.
Keywords: F44; F12; 330; Business fluctuations and cycles; Exchange rates; International topics